Circulating miR-449a predicts survival outcome for colorectal cancer following curative resection: An observational study. Issue 15 (16th April 2021) - Fu, Dengke; Chen, Yang; Xu, Dongkui
Abstract : Abstract: Previous studies showed that microRNA (miR)-449a may function as a tumor suppressor. However, the expression pattern and value of circulating miR-449a in colorectal cancer (CRC) remain unclear. Therefore, the purpose of this study was to measure circulating miR-449a level of CRC patients and evaluate its value for predicting prognosis. Plasma samples of 343 consecutive CRC patients and 162 healthy controls were obtained. Circulating miR-449a levels were measured by using real-time quantitative reverse transcription polymerase chain reactions. All enrolled patients were followed up in a regular interval after surgery. The clinical data and survival outcome of all 343 patients were collected. The correlation between circulating miR-449a level and survival outcomes was analyzed by univariate and multivariate analysis. Circulating miR-449a level in CRC patients was significantly decreased ( P  < .05) comparing with healthy controls. Low miR-449a was significantly associated with CEA and CA19-9 level (both P  < .05). Furthermore, patients with a decreased miR-449a level had a lower 5-years overall survival (OS) rate than those with a high miR-449a (67.4% vs 76.9%, P  = .03). Low circulating miR-449a level also been demonstrated as an independent risk factor for CRC in multivariate COX analysis (HR, 2.56; 95%CI: 1.15–8.63; P  < .05). Circulating miR-449a was significantly decreased in CRC patients and closely related to poor prognosis, suggesting that miR-449a might can be used as a useful diagnostic and prognostic marker for CRC.